الحماية القانونية للمرأة القطرية ضحية العنف الأسري: Legal Protection for Women Qatari victims of Domestic violence - بوسعيد, سلاف; Hj Abdullah , Raihanah; Samah, Mahamatayuding (Online Journal of Research in Islamic Studies, 2023)
Domestic violence is considered to be a fundamental factor affecting the personality of women according to their means and form of use, and violence against women within their families is a satisfactory social phenomenon, reflecting the disharmony between men and women within the family. The study was based on the nature of Qatari society; Qatari women are subjected to verbal and psychological violence in the first place. The violent use of harsh words that offend the dignity, personality and self of women extends to their neglect and disregard, which negatively affects their psychological status. The main reasons for Qatari women's exposure to violence within the family are the misconception of customs and traditions, the low religious distribution of family members, and the most prominent family differences, which increase the burden of violence. The Qatari law has attempted to address the phenomenon of domestic violence against women through the constitutional establishment of women's rights and protection against violence, and within institutions in the context of the promotion of human rights and the empowerment of Qatari women within and outside the family.